Barriers and facilitators to HIV testing in people aged 50 years and older: a systematic review. (November 2016) - Youssef, Elaney; Cooper, Vanessa; Delpech, Valerie; Davies, Kevin; Wright, Juliet
Abstract: Background: Effective therapy means that HIV-positive individuals can now experience a near normal life expectancy. Despite these advances in treatment, about one in six people living with HIV in the UK are unaware of their infection. Although the overall number of new HIV diagnoses has decreased, the number of people diagnosed at age 50 years and older is increasing. There might be unique factors associated with the decision to test for HIV in this group. This systematic review aimed to identify patient and clinician related barriers and facilitators to HIV testing in people aged 50 and above. Methods: A systematic electronic search of Medline, Embase, PsycINFO, and CINAHL was conducted on April 7, 2016. Search terms included combinations of words describing HIV, old age, and testing. Papers were assessed for eligibility (published since Jan 1, 1997, describing barriers or facilitators to testing, research in people ≥50 years, written in English). Data from eligible studies were extracted (including study design, sample size and characteristics, analysis, and reported barriers or facilitators to testing). Reported barriers and facilitators were grouped into themes, and the number of times each was reported was noted. Findings: Electronic searches identified 1752 articles, of which 14 primary studies met the inclusion criteria. A further three eligible papers were identified from reference and citation searching. 17 papers were included in the review. Most of the studies (n=14) were from the USA. The main patient barriers to non-testing were low perceived risk and not being offered or encouraged to test by a health-care professional (reported five and three times, respectively). The main clinician barrier was preconceptions about older people and discomfort discussing sexuality and risk (reported five times). Main facilitators of testing were being offered or encouraged to test by a health-care professional, previous interactions with health-care services, and high perceived risk (all reported more than five times). Interpretation: Clinicians' beliefs that people aged 50 years and older are not at risk of HIV infection, or will feel uncomfortable discussing risk and sexuality, were among the most commonly cited barriers to offering a test. However, being offered or encouraged to test by a health-care professional was the most commonly cited facilitator to testing. The divide between clinicians' preconceptions and patients' expectations might impact on testing rates. Funding: This work is part of a National Institute for Health Research doctoral research fellowship (ref DRF-2015-08-086).